Does giving segmental muscle vibration alter the response to botulinum toxin injections in the treatment of spasticity in people with multiple sclerosis? A single-blind randomized controlled trial. (September 2013) - Paoloni, Marco; Giovannelli, Morena; Mangone, Massimiliano; Leonardi, Laura; Tavernese, Emanuela; Di Pangrazio, Elisabetta; Bernetti, Andrea; Santilli, Valter; Pozzilli, Carlo
Objective: To determine if segmental muscle vibration and botulinum toxin-A injection, either alone or in combination, reduces spasticity in a sample of patients with multiple sclerosis. Design: Single-blind, randomized controlled trial. Setting: Physical medicine and rehabilitation outpatients service. Subjects: Forty-two patients affected by the secondary progressive form of multiple sclerosis randomized to group A (30 minutes of 120 Hz segmental muscle vibration over the rectus femoris and gastrocnemius medial and lateral, three per week, over a period of four weeks), group B (botulinum toxin in the rectus femoris, gastrocnemius medial and lateral and soleus, and segmental muscle vibration) and group C (botulinum toxin). Main measures: Modified Ashworth Scale at knee and ankle, and Fatigue Severity Scale. All the measurements were performed at baseline (T0), 10 weeks (T1) and 22 weeks (T2) postallocation. Results: Modified Ashworth Scale at knee and ankle significantly decreased over time ( p < 0.001) in all groups. Patients in group C displayed a significant increase of knee and ankle spasticity at T2 when compared with T1 ( p < 0.05). Fatigue Severity Scale values in groups A and C were significantly higher at T0 [A: 53.6 (2.31); C: 48.5 (2.77)] than at either T1 [A: 48.6 (2.21); p = 0.03; C: 43.5 (3.22); p = 0.03] or T2 [A: 46.7 (2.75); p = 0.02; 42.5 (2.17); p = 0.02], while no differences were detected in group B [T0: 43.4 (3.10); T1: 37.3 (3.15); T2: 39.7 (2.97)]. Conclusion: Segmental muscle vibration and botulinum toxin-A reduces spasticity and improves fatigue in the medium-term follow-up in patients with multiple sclerosis.